Quantitative analysis of the influence of middle-deep structural characteristics on shallow geothermal field - Gao, Feng; Gao, Jun; Wang, Lizhi; Bai, Huaqing; Tang, Xianchun; Qin, Junsheng; Zhang, Dailei; Yin, Xuwei; Lin, Tianyi; Liu, Qing (Frontiers in Earth Science, 2025)
The study of the shallow geothermal field can provide precise parameters for the optimization design of ground source heat pump systems, and offer scientific basis for urban energy planning and the selection of new energy stations in new areas. The middle and deep structure has a certain influence on the shallow geothermal energy, and the influence law of different structures (bedrock characteristics, fault structure) is quite different. Based on the geological structure and stratigraphic characteristics of Gaoyang geothermal field in Xiong 'an New Area, the theoretical geological model and mathematical model of different structural characteristics are constructed. The influence of bedrock burial depth and fault cutting depth on shallow geothermal field is quantitatively analyzed. The study shows that the sensitivity of the fault structure to the temperature field is about 1.9 times that of the uplift structure in the simulation of the heat flow coupling field. The contribution rate coefficient increases with the increase of temperature field depth, and the contribution rate of the fault structure to the shallow temperature field in the heat-flow coupling mode is about 13 times that of the thermal-solid coupling. The shallower the buried depth of the uplift is, the more intense its influence on the shallow temperature field will be. The influence of fault structures on the temperature field is much stronger than that of uplift structures. The seepage field of the uplift structure and the fluid in the fault structure directly affect the shallow geothermal field.